How to Manage FAN’S C Shape Canals along with S Shape Morphology in Indian Population: A Case Series and Narrative Review - Lavanya, A; Tewari, Rajendra Kumar (UI Scholars Hub, 2023)
The C-shaped root canals offer greater negotiation, debridement, and obturation difficulty as they present with intercommunications, lateral canals, and reduced dentin thickness. Objective: This case series elaborates on the recognition that these varying configurations is important to enhance adequate cleaning, shaping, and sealing of the root canal. Case Reports: On clinical examination, all the teeth showed caries were nonresponsive to sensibility tests and toother diagnostic tests, suggestive of pulp necrosis with apical periodontitis. Conventional root canal treatment with different techniques and obturation systems have been used. This case series presents the successful management of various C-shaped configurations classified by Fan et al. and emphasizes the different treatment approaches for effective therapy. The cleaning and shaping process should always follow the canal anatomy to maintain the canal shape at the same point the primary and secondary curvatures and thin interconnections are negotiated, prepared, and sealed. Conclusion: The morphological variation existence and their different types and management should be known for improved healing and enhanced success of root canal treatment.